The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1038/s41598-017-13316-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulate vacuolar ATPase blocker exhibits potent host-targeted antiviral activity against feline coronavirus

Abstract: Feline infectious peritonitis (FIP), caused by a mutated feline coronavirus, is one of the most serious and fatal viral diseases in cats. The disease remains incurable, and there is no effective vaccine available. In light of the pathogenic mechanism of feline coronavirus that relies on endosomal acidification for cytoplasmic entry, a novel vacuolar ATPase blocker, diphyllin, and its nanoformulation are herein investigated for their antiviral activity against the type II feline infectious peritonitis virus (FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 47 publications
3
63
0
Order By: Relevance
“…Moreover, diphyllin and bafilomycin showed a sustained release profile, which is advantageous toward improving the drugs' pharmacokinetics. In our previous report, we showed that diphyllin nanoparticles could enhance the compound's efficacy against the feline coronavirus, 23 and this study further verified the nanocarriers' effect against influenza virus. Other studies have shown similar benefits upon nanoparticle encapsulation of antivirals.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Moreover, diphyllin and bafilomycin showed a sustained release profile, which is advantageous toward improving the drugs' pharmacokinetics. In our previous report, we showed that diphyllin nanoparticles could enhance the compound's efficacy against the feline coronavirus, 23 and this study further verified the nanocarriers' effect against influenza virus. Other studies have shown similar benefits upon nanoparticle encapsulation of antivirals.…”
Section: Discussionsupporting
confidence: 68%
“…As the diphyllin nanoparticles were previously shown to be well tolerated in mice, 23 we further examined the applicability of the nanoparticulate V-ATPase inhibitors for influenza treatment in vivo, a mouse model of influenza infection was used. Mice were inoculated intranasally with a nonlethal dose of H1N1 virus and intravenously treated with diphyllin nanoparticles equivalent to 10 µg of diphyllin or empty nanoparticles of equivalent polymer content daily for 3 days ( Figure 6A).…”
Section: Antiviral Efficacy Of Diphyllin Nanoparticles In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Diphyllin is well tolerated in mice [43]. Delivery of diphyllin by nanoparticles increases its antiviral effects on feline CoV and it is also well tolerated in mice [45]. Niclosamide, a salicylanilide, has been used to treat parasitic helminthic infestations in humans for >40 years [46].…”
Section: Targeting Endosomal Membrane Fusionmentioning
confidence: 99%
“…In reviewing treatment options for FIP, numerous older studies describing potential treatments are mostly based on cases without a confirmed diagnosis of FIP and hampered by the lack of well-controlled clinical trials [14]. Likewise, the use of other reported treatment options is currently only supported by in vitro studies rather than through in vivo clinical studies [15,16,17,18]. Despite recent antiviral studies with GC376 and GS-441524 showing great promise against FIPV in naturally and experimentally infected cats [19,20,21], these agents have not yet obtained registration for veterinary use [22,23].…”
Section: Introductionmentioning
confidence: 99%